A Study of Web Design for Customer Billing Telephony System Using User Experience (UX) Approach - Che Pa, Noraini; Bidin, Raziera; Kamaruddin, Azrina (International Journal of Engineering and Technology, 2018)
Telecommunications industry has gone through series of development efforts to make services available to consumers and to provide quality services. The hardest challenge in telecommunications industry is to meet the customer satisfaction in billing system such as the accurate billing, easy to understand and resolving billing issue, the billing problem resolution speed, the service cost performance, rate discount degree, and rate communication. Hence, the improvement of these issues can enhance the customer satisfaction. User Experience (UX) is an approach that takes in consideration on user’s preference, emotions, physical and psychological responses, perceptions, behavior that occur before, during and after using the system in designing the user interfaces. Obviously, this creates innumerable design and experience opportunities which represent the holistic view with of the pragmatic aspect and hedonic aspect. Nowadays, UX is becoming an important issue in developing web based system and it has been discussed by many researchers. This research is focus on a study of customer billing telephony system in order to decrease the challenges in telecommunications industry. A survey conducted to collect data from the customers of telecommunication industry.  The result shows that the improvement of billing system is needed to improve the efficiency and correctness in billing process.  It is expected that by implementing the UX approach, it will improve the customer billing telephony system. In addition, it gives the positive perceptions and experiences of a service in order to increase the customer satisfaction.
Keywords: Web Design; Customer Billing Telephony System; User Experience (UX) Approach